Environmental Reporting and Board Characteristics of Indian Firm - Rakesh Yadav, Dr. Pankaj sharma (International Journal of Advanced Science and Technology, 2020)
The aim of this paper is to investigate the relationship of voluntary disclosure of environmental reporting (VDER) on board characteristics of the Indian; listed firm. A hypothesis was constructed drawing from agency and social contract theory. Using logistic regression we find that advertisement expenditure is positively and statistically significant in all the models whereas all the other board characteristics mainly women directors qualification and firm performance is negatively correlated but statistically not significant with environmental reporting. This possibly first study from Indian firm on VDER and board characteristics. The finding has important empirical support for agency theory and social contract theory. The policy makers can play important role by suggesting changes in the corporate governance mechanism of the firm by providing more incentives to agents so as make VDER fruitful to the firms.Keywords–Corporate governance, environmental reporting, social contract theory, agency theory, logistic regression, board characteristics